2012
DOI: 10.1007/s00280-012-1956-1
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of docetaxel and oxaliplatin combination in recurrent gastric cancer patients after fluoropyrimidine and/or cisplatin adjuvant treatment: a Korean Cancer Study Group Protocol ST06-02

Abstract: Docetaxel and oxaliplatin combination chemotherapy was active and tolerable in patients with recurrent gastric cancer after fluoropyrimidine and/or cisplatin-based adjuvant chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…In some phase II trials [14,15,16], a 3-week cycle SOX-based regimen for advanced patients, produced an ORR of over 45%, and a median time to progression and OS of 4.6-6.6 months and 7.8-16.5 months, respectively. The efficacy outcome of the SOX regiment in our study was comparable to that reported previously; however, the commonly observed adverse event rates were lower in our study compared to those in the trials conducted in Japan and Korea [17]. …”
Section: Discussionsupporting
confidence: 66%
“…In some phase II trials [14,15,16], a 3-week cycle SOX-based regimen for advanced patients, produced an ORR of over 45%, and a median time to progression and OS of 4.6-6.6 months and 7.8-16.5 months, respectively. The efficacy outcome of the SOX regiment in our study was comparable to that reported previously; however, the commonly observed adverse event rates were lower in our study compared to those in the trials conducted in Japan and Korea [17]. …”
Section: Discussionsupporting
confidence: 66%
“…Therefore, the role of palliative chemotherapy in the treatment of gastric cancer is especially important. The commonly used first‐line combination chemotherapy regimens consist of a fluoropyrimidine plus a platinum agent with or without docetaxel [Van Cutsem et al, ; Kim et al, ; Choi et al, ; Jiang et al, ]. However, the response to chemotherapy differs widely among GC patients, and patients who show a poor response to first‐line chemotherapy always have a poor prognosis.…”
mentioning
confidence: 99%
“…However, the overall survival of salvage RT group was comparable to other studies implementing systemic chemotherapy alone, implying that each of RT or chemotherapy may have effect on LN recurrences of gastric cancer. Median OS of the current study was 29 months which is better than those of historical controls better than those of historical controls [10-14]. Although many clinical or pathologic factors can contribute to the outcomes, aggressive treatment strategies including local and systemic modalities may be attributed to the outstanding outcomes.…”
Section: Discussionmentioning
confidence: 85%
“…Koizumi et al [13] demonstrated that combination chemotherapy with docetaxel, cisplatin, and S-1 is a well-tolerated and highly active regimen for advanced or recurrent gastric cancer, in which the median OS and PFS were 18.5 and 8.7 months, respectively. Choi et al [14] performed a phase II study of docetaxel combined with oxaliplatin for recurrent gastric cancer. With the effectiveness of combination chemotherapy, the median OS and PFS were 13.8 and 5.3 months, respectively.…”
Section: Discussionmentioning
confidence: 99%